Penerapan Jurnalisme Profetik Pada Media NU Online Jabar - Inayah, Nunung Nailul; Muhaemin, Enjang; Dulwahab, Encep (Annaba: Jurnal Ilmu Jurnalistik, 2024)
This study aims to determine the application of the traits of Shiddiq, Amanah, Tabligh, and Fathanah as the basis for prophetic da'wah strategies by NU Online Jabar in making journalistic products. This research uses Parni Hadi's prophetic journalism model as a press figure who has the idea of prophetic journalism as a way of da'wah and inheritance of the Prophet's duties to be applied in journalistic practice. The method used is descriptive qualitative with a constructivist paradigm. The results showed that NU Online West Java Media applied prophetic journalism with four strategies: Shiddiq through clear sources and news verification; Amanah by maintaining integrity and promotion strategies; Tabligh with various platforms and detailed classification; and Fathanah with journalists who are always up-to-date and utilize technology. NU Online Jabar's journalistic products are in line with the four prophetic da'wah strategies.